Reprises: Seeing like an author: early Bakhtin for anthropologists - Gershon, Ilana (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2020)
How would the anthropology of the 1990’s have been different if anthropologists understood what it meant to be a writing subject describing Others the way that Bakhtin did? These questions are undercurrents in this essay, as I summarize what early Bakhtin has to offer contemporary anthropology so that you, gentle reader, might make a more informed decision about whether it is worth tackling this exhaustingly dense prose yourself, since these are manuscripts less concerned with specific novels or utterances than with the nature of Being and the underlying relationality of the self.